Cultural translation of refugee trauma: Cultural idioms of distress among Somali refugees in displacement. (December 2017) - Im, Hyojin; Ferguson, Aidan; Hunter, Margaret
Westernized approaches to mental health care often place limited emphasis on refugees' own experiences and cultural explanations of symptoms and distress. In order to effectively assess community mental health needs and develop interventions grounded in local needs, mental health programs need to be informed by an understanding of cultural features of mental health, including cultural idioms of distress (CIDs). The current study aims to explore CIDs among Somali refugees displaced in Kenya to understand mental health needs in cultural context and serve the community in a culturally responsive and sensitive manner. This research was conducted as a two-phase qualitative study. First, key informant interviews with Somali mental health stakeholders generated a list of 7 common Somali CIDs: buufis, buqsanaan, welwel, murug, qaracan, jinn, and waali . Typologies of each CID were further explored through four focus group interviews with Somali community members. The findings from a template analysis revealed Somali lay beliefs on how trauma and daily stressors are experienced and discussed in the form of CIDs and how each term is utilized and understood in attributing symptoms to associated causes. This study highlights the need to incorporate colloquial terms in mental health assessment and to adopt a culturally relevant framework to encourage wider utilization of services and religious/spiritual support systems.